Cuban Sugar Cane Wax Acid and Policosanol Showed Similar Atheroprotective Effects with Inhibition of LDL Oxidation and Cholesteryl Ester Transfer via Enhancement of High-Density Lipoproteins Functionality. (24th February 2019) - Cho, Kyung-Hyun; Bae, Myung-Ae; Kim, Jae-Ryong
Abstract : Background . Cuban sugarcane wax acids (SCWA) and policosanol (PCO) are mixtures of higher aliphatic acids and alcohols, respectively, purified from sugarcane wax with different chief components. Although it has been known that they have antioxidant and anti-inflammatory activities, physiological properties on molecular mechanism of SCWA have been less studied than PCO. Methods . In this study, we compared antiatherogenic activities of SCWA and PCO via encapsulation with reconstituted high-density lipoproteins (rHDL). Results . After reconstitution, SCWA-rHDL showed smaller particle size than PCO-rHDL with increase of content. PCO-rHDL or SCWA-rHDL showed distinct inhibition of glycation with similar extent in the presence of fructose. PCO-rHDL or SCWA-rHDL showed strong antioxidant activity against cupric ion-mediated oxidation of low-density lipoproteins (LDL), and inhibition of oxLDL uptake into macrophages. Although PCO-rHDL showed 1.2-fold stronger inhibition against cholesteryl ester transfer protein (CETP) activity than SCWA-rHDL, SCWA-rHDL enhanced 15% more brain cell (BV-2) growth and 23% more regeneration of tail fin in zebrafish. Conclusion . PCO and SCWA both enhance the beneficial functions of HDL to maximize its antioxidant, antiglycation, and antiatherosclerotic activities and the inhibition of CETP. These enhancements of HDL functionality by PCO and SCWA could exert antiaging and rejuvenation activity.